Analysis Validation of Learning Media Quantum Phenomenon - Baiq Uswatul Khasanah; Aris Doyan; Gunawan Gunawan; Susilawati Susilawati; Kartini Kartini; Syamsul Hakim; Lalu Muliyadi (Jurnal Penelitian Pendidikan IPA, 2019)
Abstract: This study aims to produce learning media in high school grade XII science quantum phenomenon material. This research is development research that uses the research and development model of Borg and Gall with ten stages, but in this study only followed until the fifth step. Data from development research results in the form of a percentage of the validity of learning media from the validation sheet in the form of responses and suggestions obtained from the test results by material experts and media experts. This learning media is supported by a syllabus, learning implementation plans, and student worksheets as well as instruments for understanding students' concepts and critical thinking skills. The focus of this research is the validity test by material experts, media experts on the media developed. The results of the learning media validation from the test subjects were declared appropriate for use. Keywords: Learning Media; Quantum Phenomenon; Validation